2004
DOI: 10.1111/j.1365-313x.2004.02272.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel heat shock factor‐dependent genes and biochemical pathways in Arabidopsis thaliana

Abstract: SummaryIn order to assess specific functional roles of plant heat shock transcription factors (HSF) we conducted a transcriptome analysis of Arabidopsis thaliana hsfA1a/hsfA1b double knock out mutants and wild-type plants. We used Affymetrix ATH1 microarrays (representing more than 24 000 genes) and conducted hybridizations for heat-treated or non-heat-treated leaf material of the respective lines. Heat stress had a severe impact on the transcriptome of mutant and wild-type plants. Approximately 11% of all mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
360
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(396 citation statements)
references
References 50 publications
24
360
2
Order By: Relevance
“…Although these two herbicides interfere with the synthesis of branched-chain amino acids, an herbicide that targets photosystem II, bromoxynil, did not induce PEN3 expression (Glombitza et al, 2004). Abscisic acid and heat shock treatments downregulated the expression of PEN3 (see Supplemental Table 2 online) (Busch et al, 2005). Thus, PEN3 expression is altered by pathogens and a subset of abiotic stresses.…”
Section: Pen3 Encodes a Pdr-like Abc Transportermentioning
confidence: 99%
“…Although these two herbicides interfere with the synthesis of branched-chain amino acids, an herbicide that targets photosystem II, bromoxynil, did not induce PEN3 expression (Glombitza et al, 2004). Abscisic acid and heat shock treatments downregulated the expression of PEN3 (see Supplemental Table 2 online) (Busch et al, 2005). Thus, PEN3 expression is altered by pathogens and a subset of abiotic stresses.…”
Section: Pen3 Encodes a Pdr-like Abc Transportermentioning
confidence: 99%
“…The expression of most HsfA2-regulated genes appears also to be dependent on HsfA1a/HsfA1b (Busch et al, 2005). Although HsfA1a/HsfA1b are not induced by either heat or anoxia (Fig.…”
Section: Hsfa2 Overexpression Confers Tolerance To Anoxiamentioning
confidence: 99%
“…Interestingly, it seems that in Arabidopsis, different from tomato (Solanum lycopersicum; Mishra et al, 2002), there is not a unique master regulator for the Hsf-mediated heat shock response. Different Hsfs have been identified as potential crucial element for Arabidopsis response not only to heat stress (Busch et al, 2005;Schramm et al, 2006Schramm et al, , 2008Charng et al, 2007) but also to oxidative stress (Li et al, 2005;Nishizawa et al, 2008), hydrogen peroxide (H 2 O 2 ), high light (Nishizawa et al, 2006), and salt stress as well (Ogawa et al, 2007).…”
mentioning
confidence: 99%
“…It has been reported that the expression of Arabidopsis GolS1 and GolS2 is regulated by a heat shock transcription factor (HSF), such as HsfA1a, HsfA1b, and/or HsfA2 (Panikulangara et al, 2004;Busch et al, 2005;Schramm et al, 2006). Recently, we reported that the transcription of GolS1 and GolS2 is induced by a combination of high-light and heat stress or treatment with hydrogen peroxide, as is the transcription of HsfA2 (Nishizawa et al, 2006).…”
mentioning
confidence: 99%